Analisis Kesesuaian Lahan Untuk Habitat Bertelur Penyu Lekang(Lepidochelys Olivacea)Di Sebagian Pesisir Pantai Pelangi Kabupaten Bantul - Fathin, Ira Nurina; , Dra. Alif Noor Anna, M.Si (2016)
This research was conducted in the coastal areas OF Pelangi Beach, Kretek, Bantul. The aims of this research are: (1) analysis of Lepidochelys Olivacea nesting ground suitability with the appropriate physical parameters of environment, and (2) analysis of Lepidochelys Olivacea nesting ground suitability. This research used a survey method, survey to get sample data using purposive sampling method with sample consider turtle landing sites to lay their eggs (nesting ground) in the coastal areas of Pelangi Beach. Analysis of data spatial was performed using weighted tiered quantitative methods with the physical parameters used are slope of beach, sand texture, land surface temperature, and barrier of parameter is land use. The resulting suitability map was analyzed with the location of actual turtle nesting grounds in Pelangi Beach. The purpose of these analysis was to assess the accuracy of the map. The results show that the physical parameters that influence with suitability in the coastal areas of Pelangi Beach are slope of beach and land use. Most of the coastal areas of Pelangi Beach include in quite approciate class for Lepidochelys Olivacea nesting ground and patches included in suitable and not suitable class. These results indicate that an effect of parameter as slope of beach, landuse and land surface temperature can reducing the interest of the turtle to lay eggs, but they can be solved by natural spring nesting and further treatment.